Sufficiency and consistency of antenatal care services in Ethiopia: Evidence from Mini Ethiopian demographic and health survey - Dessalegn Tamiru; Mohammed Areb; Gemechis Gunja; Million Abera; Desta Asefa; Gurmesa Tura Debelew; Negalign Berhanu; Yibeltal Siraneh; Fira Abamecha; Biru Abdissa Mizana (PLoS ONE, 2025)
Background Antenatal care plays a critical role in promoting the health of mothers and infants. In Sub-Saharan Africa, about 76% of women accessing at least one visit. However, rural areas in Ethiopia face more significant challenges, including traditional beliefs, geographical distance, and the need for more awareness. Despite advancements, ensuring quality ANC for all women necessitates targeted interventions. There are needs of evidence regarding adequacy and consistency ANC services in different regions of Ethiopia. Therefore, study aimed to evaluate and compare the adequacy and consistency of ANC services across various regions in Ethiopia. Methods Data for the 2019 Mini Ethiopia Demographic and Health Survey (Mini EDHS) were collected using a cross-sectional study design. The survey included 2,918 women aged 15–49 from various regions of Ethiopia. Data analysis was carried out using STATA version 14. Descriptive statistics, such as frequencies and percentages, were used to present the background characteristics of the participants. To assess the significance of variations and associated factors, a logistic regression model was applied. Variables with a p-value of 0.25 or less in the bivariate analysis were included in the multivariable analysis. A significance level of p < 0.05 and a 95% confidence interval were used to determine the significance of the variables. Results The study surveyed 2,918 women aged 15–49, with 70.7% receiving antenatal care (ANC) from a skilled provider. Among them, 56.8% had four or more visits, and 43% started care in the first trimester. Overall, 35.8% received all routine ANC components, and 14.7% received adequate ANC services. ANC adequacy varied by region, with the highest in Addis Ababa (39.1%) and lowest in SNNPR (6.2%). About 72% of women received consistent ANC, with Addis Ababa showing the highest consistency (54.2%). Logistic regression analysis found that education status, region, wealth status, and literacy were significant factors influencing ANC adequacy. Regional disparities showed lower ANC adequacy in Oromia, Benishangul, SNNPR, and Gambela compared to Tigray. Wealthier women and those with secondary or higher education were more likely to receive consistent ANC. Conclusion The study underscored the significant impact of regional disparities, financial constraints, education levels, and geographic location on the unequal access to and quality of antenatal care (ANC) services in Ethiopia. Promoting ANC utilization, especially among women with lower education and economic disadvantages, was identified as a key priority. The study recommends targeted interventions to address service gaps for less-educated women and highlights the need for focused efforts to reduce regional disparities in both the adequacy and consistency of ANC services.